Identification of functional enhancer variants associated with type I diabetes in CD4+ T cells - Mishra, Arpit; Jajodia, Ajay; Weston, Eryn; Jayavelu, Naresh Doni; Garcia, Mariana; Hossack, Daniel; Hawkins, R. David (Frontiers in Immunology, 2024)
Type I diabetes is an autoimmune disease mediated by T cell destruction of β-cells in pancreatic islets. Currently there is no known cure, and treatment consists of daily insulin injections.Genome-wide association studies and twin studies have indicated a strong genetic heritability for type I diabetes and implicated several genes. Because most strongly associated variants are noncoding, there is still a lack of identification of functional and therefore likely causal variants. Given that many of these genetic variants reside at enhancer elements, we have tested 121 CD4+ T cell enhancer variants associated with T1D. We found four to be functional through massively parallel reporter assays. Three of the enhancer variants weaken activity while the fourth strengthens activity. We link these to their cognate genes using 3D genome architecture or eQTL data and validate using CRISPR editing. Validated target genes include CLEC16A and SOCS1. While these genes have been previously implicated in type 1 diabetes, and other autoimmune diseases, we show that enhancers controlling their expression harbor functional variants. These variants, therefore, may act as causal type 1 diabetic variants.